2008
DOI: 10.1177/0886260508323666
|View full text |Cite
|
Sign up to set email alerts
|

Play Context, Commitment, and Dating Violence

Abstract: This study develops a structural equation model to describe the effect of two groups of factors (type of commitment and play context) on the violence experienced during intimate partner conflict. After contrasting the model in adolescents and university students, we have confirmed that aggressive play and the simulation of jealousy and anger increase the risk of dating victimization during conflicts through the negative reactions that they cause. Where commitment is concerned, the results are different accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
2
16
0
3
Order By: Relevance
“…In sum, these findings add evidence showing that physical and sexual aggression peak around the ages of 16 and 17 years, and this peak may be related to specific aspects of the developmental stage. First, some authors have suggested that patterns of partner violence are different during adolescence than in adulthood, and they could reflect a more “normative” interactional style related to rudimentary means of communication to signal intimacy and resolve conflicts (González-Méndez & Hernández-Cabrera, 2009; Wekerle & Wolfe, 1999). Consequently, in the absence of other resources, aggressive behaviors become a “tool” for resolving conflicts and emotionally approaching the dating partner.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, these findings add evidence showing that physical and sexual aggression peak around the ages of 16 and 17 years, and this peak may be related to specific aspects of the developmental stage. First, some authors have suggested that patterns of partner violence are different during adolescence than in adulthood, and they could reflect a more “normative” interactional style related to rudimentary means of communication to signal intimacy and resolve conflicts (González-Méndez & Hernández-Cabrera, 2009; Wekerle & Wolfe, 1999). Consequently, in the absence of other resources, aggressive behaviors become a “tool” for resolving conflicts and emotionally approaching the dating partner.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the location of “on purpose” made it unclear if it was referring to “physically hurt” or to all the types of aggression included in the question. As a result, this item may have also captured play-fighting or “horseplay,” which has been shown to be common among adolescent dating partners 16,17 ; researchers have pointed out that the boundaries between play-fighting/flirting and actual aggression in adolescence are not always clear. 18–20 The previous question also only asked about violence perpetrated by a “boyfriend or girlfriend,” which may have inadvertently included only serious relationships and excluded more casual dating relationships.…”
mentioning
confidence: 99%
“…The gendered nature of IPV has important, and complicated, implications for prevention and intervention. Prevention programs must tread a line between equating all acts of violence, which rings false, and only taking male violence seriously, which denies women’s capacity for meaningful violence and potentially contributes to a double standard that may ultimately put women at greater risk (Gonzalez-Mendez & Hernandez-Cabrera, 2009). Intervention programs for victims and abusers must consider the meanings and impact of behaviors for the parties involved.…”
Section: Discussionmentioning
confidence: 99%